1995
DOI: 10.1002/eji.1830250902
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic death of lymphocytes in murine acquired immunodeficiency syndrome: Involvement of Fas‐Fas ligand interaction

Abstract: Murine acquired immunodeficiency syndrome (MAIDS) is caused by a defective murine leukemia virus. The disease is characterized by abnormal lymphoproliferation, impaired T and B cell function and aberrant regulation of cytokines. Both T and B lymphocytes show activated phenotypes, but undergo apoptotic death with characteristic DNA fragmentation. These results indicate the presence of a continuous activation death pathway of the lymphocytes in MAIDS. Overexpression of the bcl-2 transgene in lymphocytes showed n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

1996
1996
2000
2000

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…To assess the contribution of the CD95 system to the apoptosis of T and B cells in PP of MAIDS mice, we examined the absolute numbers and percentage of cells in PP from LP-BM5-infected B6 lpr mice in which CD95 is mutant (1). Kanagawa et al have found that murine AIDS is accelerated in CD95 mutant C57BL/6 lpr/lpr mice (23). Consistent with their findings, MAIDS was accelerated in CD95-deficient B6 lpr mice as assessed by mortality, splenomegaly, and increased number of abnormal B220 ϩ T cells (unpublished observation).…”
Section: Decrease In Numbers Of Both T and B Cells In Pp During Maidssupporting
confidence: 60%
See 2 more Smart Citations
“…To assess the contribution of the CD95 system to the apoptosis of T and B cells in PP of MAIDS mice, we examined the absolute numbers and percentage of cells in PP from LP-BM5-infected B6 lpr mice in which CD95 is mutant (1). Kanagawa et al have found that murine AIDS is accelerated in CD95 mutant C57BL/6 lpr/lpr mice (23). Consistent with their findings, MAIDS was accelerated in CD95-deficient B6 lpr mice as assessed by mortality, splenomegaly, and increased number of abnormal B220 ϩ T cells (unpublished observation).…”
Section: Decrease In Numbers Of Both T and B Cells In Pp During Maidssupporting
confidence: 60%
“…We reported that the level of CD95 is increased on splenocytes in MAIDS mice (15). Recently, Kanagawa et al have demonstrated that lpr mice deficient in CD95 exhibited drastically accelerated disease development, suggesting the involvement of the CD95 system in the regulation of the lymphoproliferation in MAIDS mice (23).…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…Recombination between the defective MAIDS virus and an endogenous sequence has been reported, suggesting that the creation of virus variants by the recombination event may play an important role in the pathogenesis and escape from host immune attack (10,13). However, we observed no such event, although the various changes of nucleotide sequences in p12 gag regions from the inoculated mutant viruses were determined by PCR amplification (data not shown).…”
mentioning
confidence: 62%